First explorations: ontogeny of central place foraging directions in two tropical seabirds. (4th April 2020) - Collet, Julien; Prudor, Aurélien; Corbeau, Alexandre; Mendez, Loriane; Weimerskirch, Henri
Abstract: A widespread hypothesis for the ontogeny of behavior and decision-making is the early-exploration-later-canalization hypothesis. It postulates that juveniles are more exploratory and adults more consistent in their behavior. In addition, it is often assumed that naïve juveniles could overcome the costs of individual experience building by copying more the decisions of others than adults (early-conformism-later-self-defining hypothesis). Here, we compare the central place foraging movements of adults and postfledging juveniles in their first flights around the colony before dispersal and migration in two sympatric species of tropical seabirds: red-footed boobies and great frigatebirds. Using GPS records of individual movements, we analyzed the foraging directions of seabirds from the colony across successive trips. Juveniles of both species showed significant within-individual consistency in foraging direction but at lower levels than adults. Juveniles leaving the colony within the same time window showed significant but low between-individual resemblance in foraging direction at levels similar to adults. In both species, homing efficiency was lower in juveniles than in adults. Juvenile foraging directions were initially influenced by wind conditions, particularly in low wing loading frigatebirds. Wind conditions progressively lost influence on juvenile foraging directions during their first weeks of flights. In contrast, within-individual consistency, between-individual resemblance, and homing efficiency did not show signs of progression in juveniles. Our results support the early-exploration-later-canalization hypothesis but not the early-conformism-later-self-defining hypothesis. Relaxed constraints on self-feeding efficiency could favor high variability in postfledging tropical seabirds. Our simple approach could be applied to further test these hypotheses by comparing strategies across a wide range of central place foragers. Abstract : Juvenile tropical seabirds were more exploratory but not more conformist than their parents in their successive excursions out of the colony. Yet juveniles homed less efficiently and were more affected by wind conditions than adults. Species differed in how juveniles used wind in early flights, consistent with their soaring flight style. The exploratory behavior in juveniles might be favored in these species through persistent parental feeding of fledged juveniles.